Indirubin regulates T cell differentiation by promoting αVβ8 expression in bone marrow‐derived dendritic cells to alleviate inflammatory bowel disease. (25th September 2022) - Zhang, Tao; Peng, Hong; Li, Yunxiang; Zhou, Xiaoqing; Pu, Wenfeng; Zhang, Yan; Du, Zhonghan; Wei, Fuxia; Li, Siqing; Zhou, Qian
Abstract: Inflammatory bowel disease is a disease that can invade the whole digestive tract and is accompanied by immune abnormalities. Immune dysfunction involving dendritic cells (DCs) and T cells is recognized as a key factor in diseases. Indirubin (IDRB) exerts antiinflammatory effects and can help in treating immune diseases. This study aimed to isolate bone marrow‐derived dendritic cells (BMDCs) using lipopolysaccharide (LPS) to obtain mature DCs (mDCs). The expression of CD80, CD86, CD40, and MHC‐II was detected using flow cytometry after treatment with IDRB. αVβ8 siRNA was used to knock down αVβ8 in mDCs, and the expression of CD80, CD86, CD40, and MHC‐II was detected. Meanwhile, DCs were co‐cultured with T cells. Then, T cell differentiation was detected using flow cytometry, and the cytokine levels were detected using enzyme‐linked immunosorbent assay. The animal model of dextran sulfate sodium (DSS)‐induced inflammatory bowel disease was established in mice. After intervention with IDRB and αVβ8 shRNA, the intestinal tissues were evaluated using H&E staining, disease activity index (DAI) score, and histological damage index, and the corresponding factors and cytokines to regulatory T cells (Treg) and Th17 were measured. The results showed that αVβ8 was expressed in immature DCs and mDCs. CD80, CD86, CD40, and MHC‐II expression decreased after IDRB treatment in mDCs. Meanwhile, the expression of TNF‐α and TGF‐β also decreased after IDRB treatment. The effect of IDRB on the expression of CD80, CD86, CD40, MHC‐II, TNF‐α, and TGF‐β in mDCs was reversed by αVβ8 siRNA. The Treg differentiation increased after IDRB treatment, while the differentiation of Th17 cells was inhibited. This effect of IDRB was reversed by mDCs after treatment with αVβ8 siRNA. In vivo experiments showed that IDRB alleviated the symptoms of inflammatory bowel disease in animals. Enteritis significantly reduced, and the effect of IDRB was reversed by αVβ8 shRNA. The results suggested that IDRB regulated the differentiation of T cells by mediating the maturation of BMDCs through αVβ8. This study confirmed the therapeutic effect of IDRB in inflammatory bowel disease and suggested that IDRB might serve as a potential drug.